Africa's Pulse, No. 24, October 2021 : An Analysis of Issues Shaping Africa’s Economic Future - Zeufack, Albert G.; Calderon, Cesar; Kubota, Megumi; Korman, Vijdan; Cantu Canales, Catalina; Kabundi, Alain Ntumba (Washington, DC: World Bank, 2021)
In 2021, Sub-Saharan Africa emerged from the recession, but its recovery is still timid and fragile. The region is projected to grow at a rate of 3.3 percent—a weaker pace of recovery than that of advanced and emerging market economies. In 2022–23, the region is projected to grow at rates below 4 percent; however, growth above 5 percent is attainable with rapid vaccine deployment in the region and thereby withdrawal of COVID-19 containment measures. In response to the pandemic, African countries are undertaking structural and economic reforms. Countries have been relatively disciplined on monetary and fiscal policies. However, limited fiscal space is handicapping African countries in injecting the fiscal resources required to launch a vigorous policy response to COVID-19.Accelerating the economic recovery in the region would require significant additional externalfinancing, in addition to rapid deployment of the vaccine. Africa’s unique conditions, such as low baseline development, preexisting climate vulnerabilities, low use of fossil fuel energy, and high reliance on climate-sensitive agriculture, pose additional challenges from climate change, but also provide opportunities to build and use greener technologies. Climate change should be considered by policymakers as a source of structural change. For instance, the energy access problem in the region can be solved by the adoption of renewable energy alongside expansion of the national grid. Policy makers need domestic and international financing to create new jobs—including green jobs. For example, in a region where much of the infrastructure, cities, and transportation systems are yet to be built, investments in climate-smart infrastructure can help cities create jobs. In resource-rich countries, wealth exposure to carbon risk can be reduced by fostering asset diversification that supports human and renewable natural capital accumulation. Financing climate change adaptation in Sub-Saharan Africa is essential, and policies to mobilize resources are critical to create more, better, and sustainable jobs.